HANUMANDHOKA DURBAR SQUARE: ENGAGING COMMUNITY AND SUSTAINABLE PRESERVATION IN A LIVING MUSEUM - Nyaupane, Pashupati (International Journal of Research -GRANTHAALAYAH, 2024)
Comprehensive investigation focuses on Hanumandhoka Durbar Square in Kathmandu, which is a UNESCO World Heritage Site and a living museum with a wealth of artistic, architectural, and historical significance. The research emphasizes the site's mythical, religious, and cultural significance as well as how it has shaped traditions and practices. One of the key objectives of the research is to examine how Hanumandhoka can preserve its original while improving to become a unique museum. The research employs an interdisciplinary methodology to investigate how contemporary advancement might coexist with the conservation of cultural heritage. The methodology incorporates qualitative research techniques including field observations, interviews, and archival research with an ethnological approach. Stakeholder theory and cultural evolutionary theory were applied to analyze the interaction between the community and the evolving cultural practices within the site. The findings highlight that to ensure that the local population actively engages in the protection and promotion of cultural assets, community engagement has to be prioritized in preservation approaches. Furthermore, educational initiatives and environmentally conscious tourism practices are essential to maintaining Hanumandhoka sustainability as a cultural heart.